Composition of phytoplankton in the Bransfield Strait and Elephant Island during austral summer of 1999 - Sánchez, Sonia (2001)
The authors inform about the composition and distribution of phytoplanktonic community between the first 75 m of depth in Bransfield Strait y around the Elephant island, during the ANTAR X expedition in the 1999 Austral Summer (22nd–29th January 1999). The higher cellular concentration (500 cel/mL) was given by the autotrophic nanoplankton, with a high density mainly on the bay stations and down the first 25 m of depth. Among the most representative species we have Leucocryptos marina, Phaeocystis antarctica, the Monadas and the pennate diatoms.